Penerapan ERP untuk Sistem Informasi Kepegawaian pada BKPSDM Kota Solok - Denny Rinaldi; Jhon Veri (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
The increasingly rapid development of information technology currently encourages organizations to implement connected information systems with one database, so that it becomes easier for several organizational devices to share data, and it is also easier to communicate. The obstacles faced when still using paper as a document medium are spending a lot of time completing documents, not being efficient in completing reports that have time limits, so that the information needed is slow and what is obtained is less than optimal. This research method is qualitative by explaining in detail about the Personnel System in personnel services in the implementation of Enterprise Resource Planning (ERP). Then the data analysis techniques used in this research are qualitative descriptive analysis, observation, interviews and documentation. In implementing this ERP, it was concluded that the personnel service application could improve human resource management thereby improving services from various areas of the organization